Identification of Soil Contamination using VLF-EM and Resistivity Methods: A Case Study - Rahmatun Inayah; Bagus Jaya Santosa; Dwa Desa Warnana; Firman Syaifuddin; Juan Pandu Gya Nur Rochman; Wien Lestari; Amien Widodo (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2019)
Hazardous waste is a waste with properties which can pollute and damage the environment, human health, and other living things. Lakardowo is a village that is suspected of being contamination by hazardous waste derived from industrial activities. Measurements with the VLF-EM and Resistivity method were used in this study. In addition, ground water level mapping and soil sampling in locations around the industry were conducted for the XRF test. Groundwater mapping results show that groundwater flow lead to the Northeast-South and Southwest of the industrial site. The soil samples that have been tested by XRF show the presence of heavy metals, wherein hazardous wastes generally contain various types of heavy metals that are conductive or have low resistivity values. Quantitative interpretation of VLF-EM data shows the presence of low resistivity anomalies at several measurement sites, which are suspected to have been contaminated with soil by waste. Resistivity data processing results, showing a low resistivity anomaly (≤ 3 Ω.m) located to the north (near an industrial site) and spreading towards the southwest along the measurement path. The result of a combination of quantitative interpretations of both methods, obtained, the direction of anomalous flow of hazardous waste moves southeastward and towards deeper soil coating following the direction of rock coating.